A Robust and Verifiable Cryptographically Secure Election Scheme - Benaloh, Josh; Fischer, Michael J. (Proceedings of 26th Symposium on Foundations of Computer Science, 1985)
This paper describes a cryptographic scheme for holding a secure secret ballot election in which all communication is public. Voters cast their votes electronically, suitably encrypted, and a “government” releases a tally and a proof of its correctness which can be verified by all.